2018
DOI: 10.15244/pjoes/77611
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Estimation Methods for Soil Organic Carbon Storage in Small Karst Watersheds

Abstract: In order to accurately estimate soil organic carbon storage (SOCS), 2,755 soil profiles and 23,536 soil samples were acquired by grid method, followed by a study on the SOCS, soil bulk density (SBD), gravel content (GC), and distribution characteristics of rock coverage (RC) in a small karst watershed (SKC). Then on the basis of soil profile summation, an investigation was done on the applicability of RC/GC-based soil type method, land utilization type method, and aspect method to the estimation of SOCS in SKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The LOC/SOC is more reflective of the effect of vegetation on soil behavior than LOC [11,50]. This study showed that the soil WSOC/SOC of the six control measures ranged from 0.31% to 0.74%.…”
Section: Impact Of Different Vegetation Restorationmentioning
confidence: 89%
See 1 more Smart Citation
“…The LOC/SOC is more reflective of the effect of vegetation on soil behavior than LOC [11,50]. This study showed that the soil WSOC/SOC of the six control measures ranged from 0.31% to 0.74%.…”
Section: Impact Of Different Vegetation Restorationmentioning
confidence: 89%
“…The soil carbon pool is about twice that of atmospheric and three times that of vegetation carbon pool, in which the soil organic carbon (SOC) contents accounts for more than 50% of the total soil carbon [2][3][4], and small changes in SOC storage will have a significant impact on atmospheric CO 2 concentrations [5][6][7][8]. However, SOC content is only a result of longterm balanced mineralization of soil organic carbon, and it is difficult to respond to short-term land use changes, and it cannot well reflect the changes of soil quality and conversion rates in a short time [9][10][11][12]. Previous studies have found that soil labile organic carbon (LOC) was more sensitive to land use change than SOC [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Any two of the Cu, Pb, Hg and Cr exhibit an extremely significant positive correlation or positive correlation, indicating that they share a similar pollutant source. The URM producing areas is a typical karst area, and there are a large number of soluble carbonate bedrocks in the territory, and the weathering of carbonate bedrock has a strong enrichment effect on the elements in the product [28,29], leading to a strong positive correlation between part of the heavy metals (Cu, Pb, Hg and Cr). In addition to natural factors, human factors also have a great influence on soil [30], long-term application of fertilizers that contain a certain amount of heavy metal pollutants like Cu, Pb, Hg and Cr also leads to a relatively strong positive correlation between these elements.…”
Section: Influencing Factors Of Heavy Metal Contents In Soil Of Urm P...mentioning
confidence: 99%
“…Soil mechanics mechanism is an important research content of soil erosion and soil and water conservation, and researchers mainly elucidate the vegetation regulating role through shear strength of the soil-root composite system [29][30][31]. Compared with the regulation mechanism of ground vegetation on soil and water loss, the study of underground root systems on soil and water conservation is much less, which is mainly caused by the study of an underground root system being relatively difficult [32].…”
Section: Study Of Soil Mechanics Mechanismmentioning
confidence: 99%